Holistic Analysis of Differentiated Learning in Pancasila Education at Sekolah Penggerak in Padang City - Fadlihi Asmi; Maria Montessori; Al Rafni; Fatmariza Fatmariza (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2025)
This study aims to describe the implementation of differentiated learning in the Pancasila education subject at “Sekolah Penggerak” (driving schools), analyze the challenges, and identify the efforts made to optimize its implementation using the indicators of content, process, product, and learning environment differentiation, focusing on students’ learning styles. The method used in this research is descriptive qualitative. The Informants in this study consisted of 30 individuals selected through purposive sampling. Data collection techniques included interviews, observations, and document analysis. The results show that the implementation of learning differentiation based on learning styles at SMAN 9 Padang and SMAN 10 Padang has been carried out, although not yet fully optimal due to shortcomings in planning and execution. In planning through teaching modules, teachers only created general guidelines. For content differentiation, teachers have provided audio-visual materials such as illustrated narrative texts, videos, and PowerPoint presentations. Teachers have applied various teaching methods, but the student worksheets (LKPD) remain uniform. Regarding product differentiation, teachers have not created varied outputs. In terms of learning environment, the arrangement of desks and chairs is sometimes inconsistent with learning activities, affecting student focus. Pancasila Education teachers at the two “Sekolah Penggerak” have made various efforts to address these challenges. In content, teachers apply classroom differentiation strategies, use movement-themed ice breakers, and attend digital training.